Clinical Significance of Melatonin in Bronchial Asthma - А. V. Budnevskiy; S. N. Аvdeev; S. А. Kozhevnikova; L. N. Аntakova; E. S. Ovsyannikov; V. V. Shishkina (Туберкулез и болезни лёгких)
The article presents the analysis of 37 publications on the effect of various hormones on the pathogenesis and course of bronchial asthma (BA), in particular melatonin. Based on analyzed publications it has been concluded that melatonin in BA can level subclinical inflammation due to its multifunctional biological and pharmacological effects. Melatonin due to its chronotropic and immunomodulatory activity normalizes sleep in patients with BA. Melatonin can be considered a promising component of the pathogenetic treatment of BA.